Design System Of Proforma Financial Statement Using The Kalman Filter - Suteja, et.al, Diana (Fakultas Teknik Universitas Widya Kartika, 2013)
Economic activity transaction data is processed to become a financial report. The preparation of financial statements for the business world is very necessary because of the financial statements reflect their economic activity and reflects the assets and liabilities they have. The financial statements have been prepared using data activity economy in the past. To find out the forecast of economic activity in the future business activities using financial statements in the past so the business can create a form of financial statements that proforma financial statements. Proforma financial statements are formal statements of financial projections for a given period and in a consistent format. With technological advances the proforma financial statement can be applied using a variety of programs so easily operated. The method used in this applicative program is using the Kalman Filter. Kalman Filter method is a method that uses prior information to forecast economic activity that will come in spite of random information in it. Achievement of objectives in this paper is to try to make a program that can be applied to predict economic activity is reflected in the proforma financial statements. Keyword: Financial Statement, Applicative Program, Proforma Financial Statement, Kalman Filter.